Interpretasi Ayat-Ayat Antropomorfisme (Studi Analitik Komparatif Lintas Aliran) - Khozinul Alim; Deddy Ilyas; Eko Zulfikar (Jurnal Semiotika Quran, 2021)
Abstract Attention to the study of the interpretation of the Qur'an, one of the problems that often occurs in different interpretations from among scholars is the interpretation of the verses of kalam (aqidah). This paper discusses the interpretation of the verses of anthropomorphism by studying comparative analysis across streams. By using descriptive-analytical methods and assisted by muqarran interpretation, it is concluded that in understanding anthropomorphic verses, there are at least four methods used by Muslim scholars, namely; take the meaning of these expressions literally (tamtsīl), based on information from the Qur’an that God is not like anything (tafwīd), use a figurative approach (ta’wīl), and deny or negate the attributes of Allah (ta’thil). From the methods used by scholars to understand the anthropomorphic verse above, at least the scholars are classified into three major groups, namely Ahlu Sunnah Wal Jama’ah, Ahlu Ta’thīl, and Ahlu Tamtsīl.